AN EVALUATION STUDY ON THE IMPLEMENTATION OF SCHOOL-BASED CURRICULUM (SBC) IN THE TEACHING OF ENGLISH AS A FOREIGN LANGUAGE IN SMP NEGERI 3 SAKRA TIMUR - ., ABDUL MAJID; ., Prof. Dr.I Ketut Seken,MA; ., Dr.Ni Made Ratminingsih, MA (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2013)
This research is to evaluate the implementation of English school-based curriculum (ESBC) in SMP Negeri 3 Sakra Timur. This evaluation research used Context, Input, Process, Product (CIPP) model from Stufllebeam (1986). Context variable is limited only in school?s geography, school?s vision and mission, school program, school management/organization, and school?s SWOT. Input as the supporting point of the program concerns curriculum (SBC), teachers? characteristics, facilities, school?s environment, and school?s budgeting. Process includes program development plan, teaching practices, assessment of students? learning, and decision making. Product or output can be measured from two aspects, namely: students? non-academic achievement, and students? academic achievement. There were 5 participants used as the subjects of the present study and they were headmaster, vice headmaster of curriculum, and 3 English Teachers in year 2012/2013. The data were collected by using questionnaire, guided interview, observation and document analysis. The data were analyzed using descriptive quantitative and qualitative method. The result shows that: (1) context, input, and product variables were positive ( + ) means good, (2) process variable was negative ( - ) means not good. It could be concluded that the English teachers in SMP Negeri 3 Sakra Timur in East Lombok regency were good enough in implementing school-based curriculum in academic year 2012/2013. From the evidence, it is suggested that English teachers should be facilitated to strengthen their awareness in teaching English.keyword : evaluation study, curriculum implementation, school based curriculum.